ANALISIS PENGARUH GREEN IMAGE TERHADAP MINAT MENGINAP KONSUMEN PASCA PANDEMI DI THE DHARMAWANGSA HOTEL JAKARTA - Darmawan, Kathrin Josephine; Ritonga, Roozana Maria (Jurnal Ilmiah Global Education, 2023)
The purpose of this research is to determine the effect of green image on consumer interest in staying after the pandemic at The Dharmawangsa Hotel Jakarta. This research uses quantitative research with convenience sampling. The survey data collection technique is by distributing questionnaires in the form of statements related to the variables discussed. This research questionnaire will be given to respondents in the South Jakarta area and surrounding areas regarding their interest in the green image. Filling out the questionnaire is done online via Google form, where the data results will later be measured using a Likert scale. The results of data collection in this research were then analyzed using the SPSS application. The research results obtained show that Green image has a positive influence on Interest in Staying at The Dharmawangsa Hotel Jakarta, with an influence of 46.9% using the coefficient of determination test. Furthermore, the suggestions given by researchers for better management in the future are to maintain the quality of the hotel environment and the hotel's green image, provide information about green image to consumers via social media, and pay more attention to hotel facilities. So this can improve the quality and green branding of The Dharmawangsa Hotel Jakarta.